2013
DOI: 10.1089/cbr.2013.1485
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole Decreases Viability of DLD-1 Colorectal Cancer Cell Line

Abstract: The aim of our study was to evaluate the impact of metronidazole (MTZ) on DLD-1 colorectal cancer cell (CRC) line. Toxicity of MTZ was determined by MTT test. Cells were incubated with MTZ used in different concentrations for 24, 48, and 72 hours. The effect of MTZ on DNA synthesis was measured as [3H]-thymidine incorporation. The morphological changes in human DLD-1 cell line were defined by transmission electron microscope OPTON 900. The influence of MTZ on the apoptosis of DLD-1 cell lines was detected by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Although, the conditions of the research was analogical to those in our research, the outcome was quite opposite ñ authors found the decrease in the viability of cells, depending on the concentration of the drug and time of incubation, with the highest value reaching 20%. In the same study authors evaluated differences in DNA synthesis using the [ 3 H]-thymidine incorporation test, which demonstrated no statistically significant changes in comparison with control cells (22). The result of the analogical test in our study was similar.…”
Section: Discussionsupporting
confidence: 68%
“…Although, the conditions of the research was analogical to those in our research, the outcome was quite opposite ñ authors found the decrease in the viability of cells, depending on the concentration of the drug and time of incubation, with the highest value reaching 20%. In the same study authors evaluated differences in DNA synthesis using the [ 3 H]-thymidine incorporation test, which demonstrated no statistically significant changes in comparison with control cells (22). The result of the analogical test in our study was similar.…”
Section: Discussionsupporting
confidence: 68%
“…In another reported article it was evaluated for its cytotoxic activity on DLD-1 colorectal cancer cell lines. They reported that the cell viability was decreased in all experimental groups when compared to control and found statistically significant 8 . MT also proved its cytotoxic potential on breast cancer cell lines, Sadowski et al reported the impact of cytotoxicity of MT on MCF-7 and MDA-MB-231 breast cancer cell lines 9 .…”
mentioning
confidence: 90%
“…F. nucleatum infections are routinely treated by MNZ 25 . MNZ represses the cell viability of DLD‐1 CRC cell lines 24 . Some therapies, such as probiotics, diets, prebiotics, stool microbiota transplantation, ursodeoxycholic acid, and engineered bacteria, can mitigate inflammatory bowel diseases by means of bile acids and gut microbiota restoration 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast activating protein 2 (Fap2) is an essential membrane protein for F. nucleatum that can encourage bacterial adhesion to colon cells, recruit immune cells, and lead to tumor development, and designing a vaccine candidate containing Fap2 B‐ and T‐cell epitopes may serve as a promising therapeutic approach to intervene in F. nucleatum ‐induced human CRC 23 . Metronidazole (MNZ) is a pivotal drug for a variety of infections, which are induced by anaerobic bacteria, besides, MTZ reduced cell viability of DLD‐1 cell lines 24 . F. nucleatum infections are routinely treated by MNZ 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation